Rancang Bangun Sistem Informasi Pengolahan Data Karyawan Absensi Berbasis Web Pada CV. Cahaya Prima Printing - Fachruddin, Ilham; Laksono., M.KOM., DR. Sularso Budi (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
A web-based employee management information system is an important requirement for companies to improve efficiency and reduce employee management weaknesses. CV. Cahaya Prima Printingas a printing company requires a web-based employee management information system to helpmanage the home manage employee data, attendance and work schedules. This study aims to designand implement a web-based employee management information system at CV. Prime Light Printing.The research methodology used is a systems approach, with stages of user needs analysis, businessprocess analysis, database design, interface design, system implementation, system testing andevaluation. The results of the study show that a web-based employee management informationsystem can help CV. Cahaya Prima Printing in managing employee data effectively and efficiently.This system has features that can help employee management, such as attendance management,work schedule management, employee permissions and menu management. System testing showsthat this system runs well and is reliable. Suggestions for the development of this system are toimprove system security so that employee data is properly maintained.